The EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Suryadi, Suryadi; Hamdani, M. Iqbal Ibrahim; Fuad, Akhmad Dzukaul (Jurnal Kiprah Pendidikan, 2025)
History education has a strategic role in shaping character, national identity, and developing students' critical thinking skills. However, the dominance of the lecture method often results in students being less active in the critical thinking process. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model in improving students' critical thinking skills in History subjects at SMK Muhammadiyah-Kalisat-Jember. This study uses a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The subjects of the study were 60 grade XI students who were divided into an experimental group (using the PBL model) and a control group (using conventional methods). Data collection was carried out through a critical thinking essay test based on Ennis indicators and analyzed using parametric statistical tests. The results showed a significant increase in critical thinking scores in the experimental group compared to the control group (p = 0.000). Therefore, the PBL model has proven effective in improving students' critical thinking skills and can be used as an alternative strategy for contextual and participatory history learning.